Historical Perspective of Kurdistani Mastura - Salih, Pazhara Mamnd Salih (Sulaimani Journal for Humanities, 2026)
In the first half of the nineteenth century, in the Kurdish context, Mah Sharaf Khanum, also known as Mastura Kurdistani (1805-1848), emerged as the only female literary writer and historian. During the period, girls' literacy was taboo in Eastern societies, but it had not become part of the culture even in the West. Our Kurdish woman not only was able to cross the boundaries of literacy but also became the owner of written works in the fields of history, poetry, and Sharia. Mastura's importance is desired to be determined twice, once as a woman's will and ability, and once as her written works. This research analyzes and compares the existence of Mastura and her historiographical perspective and historical manifestations. Mastura's historical work, History of Ardalan (Tarikh Akrad) is the fifth book of Kurdish history, it is built on the evaluation of the knowledge of the history of Zabda al-Tawarikh and the history of Lab al-Tawarikh, as well as the presence of the historian in the events. It includes the political history of the Ardalan dynasty. It has the stamp dominated by family and regional history. The influence of the traditional Iranian-Islamic historiography is evident in the writing style of its history. The geographical area of Ardalan's history revolves mostly around the areas under the rule of the Ardalan Empire, with a slight extension beyond the borders of the Empire to the Baban Empire and Iran. The period area of the history of the Ardalans covers the period from the beginning of their rule to the year of the sunset of their government around the year (1848). As a historian, Mastura expresses several ideological tendencies behind the historical narrative that legitimize the continuity of princely authority for the Empire she belonged to.